Multi-omics analysis reveals Angelica dahurica radix extract alleviates migraine in rats via gut microbiota-metabolome-gut-brain axis regulation - Lian, Yan; Gan, Zhengkun; Sun, Jieyu; Zhao, Jiawen; Li, Qing; Shen, Xile; Xue, Mingdong; Li, Junke; Luo, Jiaxin; Liu, Xinyu; Feng, Wuwen; Jiang, Guihua (Frontiers in Pharmacology, 2025)
BackgroundEmerging evidence links gut-brain axis dysregulation to migraine pathogenesis. Angelica dahurica Radix (Baizhi) demonstrates clinical efficacy in migraine management, yet its mechanisms involving gut microbiota-metabolite crosstalk remain unelucidated.MethodsA nitroglycerin (NTG)-induced migraine rat model was established. Migraine behaviors were video-recorded. Enzyme-linked immunosorbent assay (ELISA) was used to quantify neuroinflammatory and neurotransmitter markers (5-HT, CGRP1, TNF-α, NO, PGE2, DA) in plasma and brain tissue. Intestinal barrier integrity was evaluated by immunohistochemical staining of tight junction proteins (Occludin/ZO-1) and hematoxylin-eosin (H&E) staining of colonic tissue. Gut microbiota composition was analyzed via 16S rRNA gene sequencing of fecal samples, and serum metabolomic profiles were characterized using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF MS). Multi-omics data were integrated to identify key therapeutic targets and pathways.ResultsBaizhi alleviated migraine behaviors (head-scratching frequency reduced) and normalized neurochemical dysregulation (plasma and brain tissue 5-HT, CGRP1, TNF-α reduced vs. model). It restored intestinal barrier integrity via Occludin/ZO-1 upregulation and suppressed colonic inflammation. Gut microbiota analysis demonstrated that Baizhi increased the abundance of Firmicutes and beneficial genera, such as Lactobacillus and Ruminococcus_gnavus_group, while decreasing Bacteroidetes. Gut microbiota remodeling correlated with F/B ratio elevation and Lactobacillus enrichment. Key regulated pathways included tryptophan metabolism (5-HT synthesis) and mitochondrial-associated arginine-proline metabolism (NO regulation).ConclusionBaizhi alleviates migraine through multi-target coordination: reinforcing gut barrier function, enriching anti-inflammatory Lactobacillus, and restoring neurotransmitter/neurovascular homeostasis through 2-AG-mediated CGRP1 inhibition. These findings bridge traditional herbology with modern neuromicrobiology, positioning BZ as a promising gut microbiota-modulating therapy for migraine.